PENGARUH WAKTU APLIKASI PASTA CANGKANG TELUR BEBEK (Anas platyrhynchos) TERHADAP KEKERASAN PERMUKAAN EMAIL GIGI SETELAH APLIKASI BLEACHING HIDROGEN PEROKSIDA 40% - Hifzil Fahmy; Fitri Yunita Batubara (Universitas Baiturrahmah, 2022)
Introduction: The use of remineralization materials can increase enamel hardness which decreases after demineralization process. The low enamel hardness value affects the tooth sensitivity level. Duck eggshell which contains 94% calcium carbonate can be used as a remineralization material. This study aims to compare the differences in application time of duck eggshell paste to enamel hardness after application of 40% hydrogen peroxide bleaching agent. Methods: This study was an experimental laboratory with pre and post test control group design. Twenty-four crowns of maxillary premolars were embedded in blocks of acrylic resin and divided into four groups. A bleaching agent containing 40% hydrogen peroxide was then applied three times for 15 minutes. The hardness of enamel was measured using a Microvickers Hardness Tester. The remineralization process used duck eggshell paste according to groups (15 minutes, 30 minutes, 60 minutes, and immersion in artificial saliva) for 7 days. Then the hardness of the enamel was measured again. Results: The paired t-test results showed that all groups experienced a significant increase in the mean email hardness (p<0,05). The results of the one way ANOVA test showed that there were significant differences in all groups (p=0,009). The results of LSD's post hoc test showed that there was a significant difference in the 30 minutes and 60 minutes groups against the control group. Conclusion: In this study, the use of 3% hydroxyapatite paste for 30 minutes showed the highest increase in enamel surface hardness after the application of 40% hydrogen peroxide.